Reinterpreting Abu di Ateh Tunggua: Power Relations and Male Responsibility in the Minangkabau Matrilineal System - Rozalvino, Rozalvino; Sunarto, Bambang; Indrasastra, Andar; Sukerta, Pande Made (Utan Kayu Publishing, 2026)
This article examines the concept of Abu di Ateh Tunggua as a relational framework for understanding male position within the Minangkabau matrilineal kinship system. The role of the sumando has frequently been interpreted as a symbol of fragility or marginal status within customary structures. Using a qualitative, literature-based approach and conceptual analysis of customary norms, proverbial expressions, and the sumando typology, this study argues that Abu di Ateh Tunggua functions as an ethical metaphor that signifies responsibility, prudence, and relational awareness rather than structural subordination. In the Minangkabau context, men are not vested with proprietary authority within the wife’s lineage; instead, their legitimacy is grounded in moral obligations toward the nuclear family and the broader kin network. The article further identifies transformations in male roles in response to urbanization, education, and migration, highlighting ongoing negotiations between customary values and contemporary social change. These findings contribute to discussions of masculinity in matrilineal societies by demonstrating that authority may be constructed through social responsibility and collective recognition rather than ownership. The study underscores the importance of interpreting cultural expressions as analytical tools for examining power relations within indigenous kinship systems.